Hadra ritual practice: Cultural significance and continuity in the Deger pilgrimage center of Amhara, Ethiopia - Habtamu Wondimu; Endris Kassaw; Girum Melkamu (Heliyon)
This study investigates the Hadra ritual practices at the Deger pilgrimage center in Amhara, Ethiopia. It examines the basic activities and assesses changes and continuities. Using a qualitative approach and ethnographic design, the study identifies various activities as fundamental components of the Hadra ritual, including greeting, tent-making, coffee preparation, chewing, menzuma, odious, drumming, zar, food preparation, gift-giving, and blessings. The Hadra ritual promotes social cohesion, economic well-being, infrastructure development, and spiritual fulfillment for the local community. Despite changes caused by modernization and foreign influences, the rituals persist. Changes include increased participation, gifts, ethical adjustments, and the emergence of antagonism (Wahhabists), and government interventions. The Deger communities have practiced the Hadra ritual for an extended period, and it continues with some alterations due to foreign theological influences. Recommendations include raising awareness, establishing museums, renovating the pilgrimage center, and documenting to protect Hadra ritual practices.